2021
DOI: 10.5114/hm.2021.100321
|View full text |Cite
|
Sign up to set email alerts
|

Weekly variations of biomechanical load variables in professional soccer players: comparisons between playing positions

Abstract: Purpose. The purpose of the present study was fourfold: (i) to describe the weekly variations of acute external load measures during a professional soccer season; (ii) to analyse the variability of external load measures within weeks; (iii) to analyse the acute:chronic workload ratio of players during the process; and (iv) to analyse the differences of external load measures between playing positions. Methods. Twenty professional soccer players (age: 24.9 ± 3.5 years; body mass: 71.6 ± 18.7 kg; height: 168.8 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
13
3
Order By: Relevance
“…These findings are in line with previous studies monitoring workload, supporting that overall ACWR in trainings should be maintained within the ‘ sweet spot’ zone of 0.8–1.3 to minimize injury risk for players during the pre-season and in-season periods [ 11 , 17 , 41 ]. Our results also contrast with some previous study results [ 15 , 18 , 35 ]. Uday et al [ 15 ] showed that the DF had the lowest value in ACWR (1.09 AU) with professional players from a team in First Portuguese League.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings are in line with previous studies monitoring workload, supporting that overall ACWR in trainings should be maintained within the ‘ sweet spot’ zone of 0.8–1.3 to minimize injury risk for players during the pre-season and in-season periods [ 11 , 17 , 41 ]. Our results also contrast with some previous study results [ 15 , 18 , 35 ]. Uday et al [ 15 ] showed that the DF had the lowest value in ACWR (1.09 AU) with professional players from a team in First Portuguese League.…”
Section: Discussioncontrasting
confidence: 99%
“…When analysing such workload measures and player positions together, studies are scarce [ 4 , 15 17 ]. Recently, it was found that defenders presented higher values of ACWR values than midfielders and strikers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variations of training intensities [ 14 ] and well-being outcomes [ 15 ] in soccer players have been described. In youth, well-being scores seem to be more stable in the middle of the season, while in early and ending phases of the season presents greater variability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…playing position [33], age, and division in which each player participates, as all the above will contribute to the safe and successful return to training and competition. Lastly, further investigation is needed using GPS technology to evaluate to what extend the external load of the infected players was affected.…”
Section: Discussionmentioning
confidence: 99%